2021
DOI: 10.1177/00220345211046590
|View full text |Cite
|
Sign up to set email alerts
|

Activated Epithelial FGF8 Signaling Induces Fused Supernumerary Incisors

Abstract: FGF8, which is specifically expressed in the dental epithelium prior to the E12.5 bud stage, is a key player during odontogenesis, being responsible for the initiation of tooth development. Here, to investigate the impact of persistent FGF8 signaling on tooth development, we forcibly activated FGF8 signaling in the dental epithelium after the bud stage by generating K14-Cre;R26R-Fg8 mice. We found that a unique type of fused supernumerary incisors is formed, although morphologically resembling the features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
0
0
Order By: Relevance
“…Although we did not find FGF8 variants in our study, Chen et al [44] examined FGF8 using the mouse model and found a unique type of fused supernumerary incisors of the dens invaginatus phenotype. FGF8 is expressed in dental epithelium and is associated with tooth development [45]; it may represent a similar mechanism in terms of tooth development.…”
Section: Discussioncontrasting
confidence: 72%
“…Although we did not find FGF8 variants in our study, Chen et al [44] examined FGF8 using the mouse model and found a unique type of fused supernumerary incisors of the dens invaginatus phenotype. FGF8 is expressed in dental epithelium and is associated with tooth development [45]; it may represent a similar mechanism in terms of tooth development.…”
Section: Discussioncontrasting
confidence: 72%